The Effect of Red Ginger (Zingiber officinale var. rubrum rhizoma) on Neutrophil Levels After Eccentric Exercise in Support of SDG 3 - Rizky Patria Nevangga; Nur Shanti Retno Pembayun; Ananda Perwira Bakti; Ulya Asyrofa; Kandilia Sahani (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: Exercise-induced muscle damage (EIMD) following eccentric exercise triggers an acute inflammatory response characterized by increased neutrophil infiltration. Although non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used to manage inflammation, their prolonged use may cause adverse effects. This study aimed to analyze the effect of red ginger (Zingiber officinale var. rubrum) extract on plasma neutrophil levels after eccentric exercise in untrained individuals as a natural anti-inflammatory strategy supporting SDG 3 (Good Health and Well-being). Method: The experimental study employed a randomized pretest–posttest control-group design involving 30 untrained medical students from Universitas Negeri Surabaya. Participants were randomly assigned to either a control group (placebo) or an experimental group receiving red ginger extract (n = 15 each). Blood samples were collected before exercise and after intervention to determine plasma neutrophil levels. Data were analyzed using normality tests followed by paired-sample t-tests with SPSS version 26. Results: The normality test confirmed that all variables were normally distributed (p > 0.05). The control group showed no significant change in plasma neutrophil levels after eccentric exercise (p = 0.820). In contrast, the experimental group demonstrated a significant reduction in neutrophil levels following red ginger supplementation (p < 0.001), indicating a decreased inflammatory response after exercise-induced muscle damage. Novelty: The study demonstrates the anti-inflammatory potential of red ginger extract using plasma neutrophil count as an early biomarker of EIMD after eccentric exercise. The findings provide evidence for a safe, affordable, and locally available natural alternative to conventional anti-inflammatory medication, contributing to healthier exercise recovery and supporting Sustainable Development Goal 3.